Literární dystopie a pokusy o její vymezení ve světovém a českém kontextu || Literary Dystopia and Attempts to Define It in the International and Czech Contexts - Olga Pavlova (Slovo a Smysl, 2018)
This article deals with anti-utopian and dystopian literature, development of the genre and attempts at its definition. The first part contains a description of attributes characteristic of the genre: newspeak, the petrified world, and the division of the world into two fields (Us vs. Them). The author then devotes attention to previous theoretical definitions of dystopia and anti-utopia, including an historical mapping of research in foreign, mainly English studies: works by George Woodcock, Fred Polak, Mark Hillegas, Krishan Kumar, Lyman Tower Sargent and others. The survey of research in the Czech academic field is based on texts by Milada Genčiová, Daniela Hodrová and Petr Hrtánek. In conclusion, the author describes the differences between anti-utopia and dystopia, their delimitation as specific genres, proceeding primarily from the theory of petrified worlds. She also stressess the importance of a political reading of the dystopian and anti-utopian literature based on the close relation between the real world and fiction in this genre.